Optimal carbon taxes and foreign aid - Geir H. M. Bjertnæs (Statistics Norway, Research Department, 2024)
This article explores whether altruistic preferences toward households in poor high-temperature countries stimulate global warming policies within rich low-temperature countries that avoids damage from global warming. The article analyzes optimal carbon taxes on commodities within such rich low-temperature countries when damage inflicted upon poor high-temperature countries are accompanied with foreign aid. The article contributes to the literature by identifying two cases where the second-best optimal carbon tax for such rich countries exceeds the marginal damage inflicted on poor countries. First, when rich countries place a higher altruistic welfare weight on environmental damage than on economic well-being within poor countries. Second, when foreign aid is hampered by taxes within aid-receiving countries. The article also identifies cases where the Pigouvian tax implements the social planner solution. Hence, altruistic preferences and foreign aid contributes to solve the free-rider problem associated with global warming.
Keywords: H2; H21; H23; Q58; R48; 330; Optimal taxation; Foreign aid; Carbon tax; Global warming; Free-riding